2014
DOI: 10.1371/journal.pone.0093253
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Health Expenditure and Rural Household Impoverishment in China: What Role Does the New Cooperative Health Insurance Scheme Play?

Abstract: ObjectiveTo determine whether the New Cooperative Medical Insurance Scheme (NCMS) is associated with decreased levels of catastrophic health expenditure and reduced impoverishment due to medical expenses in rural households of China.MethodsAn analysis of a national representative sample of 38,945 rural households (129,635 people) from the 2008 National Health Service Survey was performed. Logistic regression models used binary indicator of catastrophic health expenditure as dependent variable, with household c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
148
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(167 citation statements)
references
References 21 publications
17
148
2
Order By: Relevance
“…However, evidence indicates that households covered by the NRCMI had similar levels of catastrophic health expenditure and medical impoverishment as those without health insurance [12] and the coverage of NRCMI showed no financial protection for households with chronic diseases [13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, evidence indicates that households covered by the NRCMI had similar levels of catastrophic health expenditure and medical impoverishment as those without health insurance [12] and the coverage of NRCMI showed no financial protection for households with chronic diseases [13]. …”
Section: Introductionmentioning
confidence: 99%
“…7 Catastrophic health expenditure and rural household impoverishment study done in China concluded that higher percentage of households experiencing catastrophic health expenditure and medical impoverishment correlates to increased health care need. 8 This study was limited in Information on social security schemes availed by families which would have given exact insight into out of pocket expenditure on health.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the analysis period in Wagstaff and Lindelow (2008), ), Lei and Lin (2009), Shi et al (2010, ), Lu et al (2012), Li and Zhang (2013, Li et al (2014), Lei and Lin (2009), Cheng et al (2015), Ma (2016 is around the period from 2000 and 2006, therefore the impact of NCMS on health service utilization is not clear in the long-term. Third, it is thought that the demand of health care may differ by individual characteristics.…”
Section: Introductionmentioning
confidence: 99%